Impact of Abdominal Adipose Depots and Race on Risk for Colorectal Cancer: A Case-Control Study. (19th May 2017) - Gomez-Perez, Sandra L.; Chaudhry, Vivek; Mar, Winnie; Patel, Bimal; Fantuzzi, Giamila; Freels, Sally; Braunschweig, Carol A.
ABSTRACT: Visceral adipose tissue (VAT) but not subcutaneous adipose tissue (SAT) is associated with obesity-related diseases including colorectal cancer (CRC). Superficial SAT (SSAT) and deep SAT (DSAT), components of SAT, also appear to independently influence disease risk. These abdominal adipose tissues (AATs) are not extensively studied in connection with CRC and have not been explored in the United States despite known racial variations in body composition. We conducted a case-control study that compared associations between AAT with CRC risk and race of African-American (AA) and non-Hispanic white (NHW) men with incident CRC matched by age, body mass index, and race ( N = 158, 79/group). Cross-sectional computed tomography images were used for assessment of AAT. Overall cases and controls had similar VAT areas (140 ± 192 vs 149 ± 152 cm 2, P -value = 0.93); however, cases had lower SSAT than controls (88 ± 39 vs 112 ± 65 cm 2, P < 0.01). Among controls, AA had significantly lower VAT (114 ± 168 vs 180 ± 167, P < 0.01) than NHW. Conditional logistic regression revealed that AA men with greater SSAT had lower odds for CRC (odds ratio [OR]: 0.24, 95% confidence interval [CI] 0.07–0.85). Our findings indicate that VAT does vary between cases and controls by race; however, this variation is not a risk factor for CRC. The negative association between CRC and SSAT in AA men warrants further investigation.